The Action Parameters, ε0-1& μ0 of Cosmic Ether Tension Field, are Behind the Emergence of all Observable Realities - Roychoudhuri, Chandrasekhar (European Journal of Applied Sciences, 2024)
The paper presents the case that physics is already and effectively unified by the energetic tension field, Cosmic Ether. We identify this integrating power of ether first, by re-defining the action generating parameters of this energetic tension field as the electric-tension, ε0-1, and the magnetic-resistance, μ0, while re-deriving the Maxwell’s wave equation in analogy with the mechanically stretched string, where the c02 = ε0-1/μ0. Then, replacement of c02 by ε0-1/μ0 and m0 by E/c02 = E(μ0/ε0-1), one can find that almost all working physics theories are being energized by ε0-1 and μ0. To complete the unification, we can now postulate that the particles are also freely propagating EM waves, but they are spatially localized as close-looped in-phase, (CLIP) torus-like complex propagation modes of ether. Because of their CLIP mode structure, they have space-finite spatial structures and remain spatially stationary in the absence of any spatially influencing potential gradients (forces) in their vicinity. Particles’ harmonic phase driven interactions between quantum particles gives birth to the appearance of wave-particle duality. There is no need for the confusing and unnecessary de Broglie’s Pilot Wave. The inertia to spatial motion of CLIP modes automatically accommodates Newton’s laws of motion. The cosmic universality of Maxwellian wave velocity, and particles as CLIP modes, jointly accommodate the two key postulates of special relativity without the need for unphysical four-dimensionality. The observable universe is represented only by its diverse oscillatory excited states. The stable and stationary Cosmic Ether keeps holding 100% of its energy all the time. We do not need to keep searching for Dark Energy and Dark Matter. We have proposed a one-way light pulse propagation experiment to directly validate the existence of ether, rather than approaching Michelson’s way of measuring the ether drag. We have identified a good number of examples of working theoretical expressions in terms of ε0-1 and μ0 and presented our critical views in physics thinking, belonging to Classical, Relativity, Quantum and Cosmology Physics.